Emotion regulation and delusion-proneness relate to empathetic tendencies in a transdiagnostic sample - Herms, Emma N.; Bolbecker, Amanda R.; Wisner, Krista M. (Frontiers in Psychiatry, 2022)
Empathetic tendencies (i.e., perspective taking and empathic concern) are a key factor in interpersonal relationships, which may be impacted by emotion regulation (i.e., reappraisal and suppression) and mental health symptoms, such as psychotic-like experiences. However, it is unclear if certain psychotic-like experiences, such as delusion proneness, are still associated with reduced empathetic tendencies after accounting for emotion regulation style and dimensions of psychopathology that are often comorbid. In the current study, linear models tested these associations in a transdiagnostic community sample (N=128), using the Interpersonal Reactivity Index, Emotion Regulation Questionnaire, and the Peter’s Delusion Inventory. Results indicated that perspective taking was positively associated with reappraisal and negatively associated with delusion-proneness, after controlling for age, sex, race, intelligence, and symptoms of anxiety and depression. A significant change in R2 supported the addition of delusion-proneness in this model. Specificity analyses demonstrated perspective taking was also negatively associated with suppression, but this relationship did not remain after accounting for the effects of reappraisal and delusion-proneness. Additional specificity analyses found no association between empathic concern and reappraisal or delusion-proneness but replicated previous findings that empathic concern was negatively associated with suppression. Taken together, delusion-proneness accounts for unique variance in perspective taking, which can inform future experimental research and may have important implications for psychosocial interventions.